Right ventricular improvement is associated with left ventricular diastolic function and size enhancement in PAH patients: an echocardiographic study. (14th October 2021) - Fauvel, C; Raitiere, O; Si-Belkacem, N; Viacroze, C; Artaud-Macari, E; Schleifer, D; Dominique, S; Bauer, F
Abstract: Background: While pulmonary vasodilation therapy improves right ventricular (RV) function in pulmonary arterial hypertension (PAH), data regarding left ventricular (LV) function remain sparse. Purpose: We aimed to investigate whether PAH therapy improve LV function in PAH patients. Methods: Between 2002 and 2020, all incident PAH patients from one PH referral centers were included, treated and followed-up according to current ESC/ERS guidelines. All patients had comprehensive echocardiography both investigating right and left ventricular function before and after 1-year of vasodilation therapy. In addition to RV echocardiographic evaluation, we focused on LV ejection fraction from Modified Simpson method, LV diameters by M-mode, transmitral pulsed-wave E/A ratio, Flow to tissue Doppler imaging E/e' ratio, and left atrial size. Results: 126 patients were included (63% female, 57±17 yo), mainly from connectivite tissue associated and idiopathic PAH (24% and 28% respectively) causes. Compared to baseline, 1-year NYHA functional class (p<0.01), NTproBNP plasma level (p<0.001), invasive mean pulmonary arterial pressure (p<0.01) and cardiac index (p<0.01) significantly improved. While LV ejection fraction (p=0.68), LV end-diastolic diameter (p=0.11) as well as LA area and volume (p=0.09) were not significantly enhanced under vasodilation therapy, LV diastolic function, assessed by mitral E wave (p<0.01), tissue doppler imaging mitral e' wave (p=0.04), and E/A ratio (p=0.045) were significantly improved at 1-year. There was a significant correlation between LV end-diastolic diameter (p<0.001) and RV end-diastolic area (p<0.001) owing to the normalization of right- to left ventricular interdependence, as well as between mitral E wave and TAPSE (p=0.045). Conclusion: By improving RV function, PAH vasodilation therapy enhances LV size and diastolic function and normalizes the biventricular interdependence. Funding Acknowledgement: Type of funding sources: None.